2007
DOI: 10.1016/j.entcs.2007.01.039
|View full text |Cite
|
Sign up to set email alerts
|

Providing Data Structure Animations in a Lightweight IDE

Abstract: This paper presents the data structure animation tool jGRASP, which can automatically generate multiple synchronized views while the underlying code is being developed. The seamless integration of the the IDE with pedagogically effective software visualizations makes jGRASP an interesting tool for both educators and students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Four controlled experiments were conducted and the results of all four showed that the data structure viewers in jGRASP had a statistically significant positive effect on student performance [22,23,24]. Specifically, students using the data structure viewers were able to write new code faster and with fewer errors, as well as find and locate more errors in a shorter amount of time.…”
Section: B Dynamic Software Visualization and Animationmentioning
confidence: 95%
“…Four controlled experiments were conducted and the results of all four showed that the data structure viewers in jGRASP had a statistically significant positive effect on student performance [22,23,24]. Specifically, students using the data structure viewers were able to write new code faster and with fewer errors, as well as find and locate more errors in a shorter amount of time.…”
Section: B Dynamic Software Visualization and Animationmentioning
confidence: 95%